Modeling Mathematics Performance Between Rural and Urban School Using a Fuzzy Logic Approach / Nor Azriani Mohamad Nor ...[et al.] - Mohamad Nor, Nor Azriani; Azizan, Azlinda; Moktar, Balkiah; Abdul Aziz, Azlan; Mohd Nasir, Diana Sirmayunie (UiTM Cawangan Perlis, 2021)
This study concerns competitiveness in Sijil Pelajaran Malaysia (SPM) performance between two different schools in Kedah, Malaysia, focusing on Mathematics scores. There are two different schools selected namely SMK Sungai Layar and SMK Bandar Sungai Petani. SMK Sungai Layar is a rural school while SMK Bandar Sungai Petani is an urban school. The objectives are to determine which schools between urban and rural schools perform better in mathematics subjects and classify students' performance on Mathematics subject using Fuzzy Logic. It is found that the performance of urban school was better than the rural school. As for rural school, the performance was moderate. The percentage of Mathematics value for SMK Bandar Sungai Petani is higher than SMK Sungai Layar. The number of students from an urban school who got a good score was double from the number of students from rural schools. The results show that the students from the urban school have excellent flexibility and reliability in Mathematics subject.